PID Controller Based Thermal Sensor for Cost Effective Cooling (International Journal of Food and Nutritional Sciences, 2022)
By 2050, the electricity demand from the usage of Air conditioning (AC) units will be tripled. This demand for cooling is particularly important in hot environment country like India, wherein it is estimated a 45% rise in usage of AC units. Optimal usage of these AC units, will not only benefit the environment, but also delay the probable installation of new power plants in future. In this paper, an objective function is developed for optimal working of AC. A combination of D6t thermal sensor, PIR sensor and ultrasonic sensor were used for human and ambience detection, upon which a PID controller will tune the desired set value for the AC unit. In this work, three case studies were taken such as Home, Lecture Hall and Commercial Space, where it is compared with and without sensors. From the result obtained, it is observed that the power consumption is very much reduced and also brings the cost saving over a time period